EDUKASI PROTOKOL KESEHATAN MELALUI GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN ONLINE MEMUAT PEMBUATAN HANDSANITIZER ORGANIK DARI DAUN KELOR - Dyah Ayu Fajarianingtyas; Jefri Nur Hidayat (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
In the end, covid 19 caused the world to change very quickly, this had an impact on the world of education, one of which was learning activities involving the use of hands that had to be in sterile conditions so hand sanitizer was needed. Educational activities are still carried out by the PMA Learning Guidance Institute located at Jalan Attorney General Suprapto No. 14 Pajagalan Seumenep. The problems that will be raised in this training regarding educational services are (1) the absence of health protocol education in terms of making organic hand sanitizer from Moringa leaves; (2) the lack of students' skills in the use of natural materials and their functions. This training aims to improve knowledge and skills in Health protocol education by utilizing organic materials. The benefit of this activity is that it can increase students' knowledge and skills in making organic hand sanitizers from Moringa leaves. The method used to solve these problems is through mentoring activities to make hand sanitizers with organic ingredients from Moringa leaves which are packaged in the form of training through the Google Classroom platform. The change in the community's paradigm due to the impact of covid 19 can be overcome by providing education to students that Moringa leaves can be processed into alternative hand sanitizer products that can be applied during the COVID-19 pandemic. The training is carried out using demonstration and experimental methods. The hand sanitizer made in this training program provides a sense of security for the skin because it contains organic ingredients. The participants of the training in making hand sanitizers already know about implementing this experiment using organic materials. Students are very skilled and get benefits after making organic hand sanitizer from Moringa leaves by 83.3%. --- Pada akhirnya dari covid 19 menyebabkan dunia berubah sangat cepat, hal ini memberikan dampak terhadap dunia pendidikan, salah satunya yaitu kegiatan belajar yang melibatkan penggunaan tangan harus dalam kondisi steril sehingga dibutuhkan handsanitizer. Aktivitas Pendidikan tetap dijalankan oleh Lembaga Bimbingan Belajar PMA yang berlokasi di Jalan Jaksa Agung Suprapto No 14 Pajagalan Seumenep. Masalah yang akan diangkat pada pelatihan ini mengenai layanan pendidikan yaitu (1) belum adanya edukasi protokol kesehatan dalam hal pembuatan handsanitizer bahan organik dari daun kelor; (2) kurangnya keterampilan siswa dalam upaya pemanfaatan bahan alam beserta fungsinya. Pelatihan ini bertujuan meningkatkan pengetahuan dan keterampilan edukasi protokol Kesehatan dengan memanfaatkan bahan organik. Manfaat kegiatan ini yaitu dapat menambah pengetahuan dan keterampilan siswa membuat hand sanitizer bahan organik dari daun kelor. Metode yang digunakan untuk menyelesaikan permasalah tersebut melalui pendampingan aktivitas  pembuatan hand sanitizer bahan organik dari daun kelor yang dikemas dalam bentuk pelatihan melalui platform google classroom. Perubahan paradigma masyarakat akibat dampak covid 19 dapat diatasi dengan cara pemberian edukasi kepada siswa bahwa daun kelor dapat diolah menjadi alternatif produk hand sanitizer yang dapat diaplikasikan dalam masa Pandemi covid 19. Pelatihan dilakukan menggunakan metode demonstrasi dan eksperimen. Hand sanitizer yang dibuat pada program pelatihan ini memberikan rasa aman bagi kulit karena kandungan bahan organik. Peserta pelatihan pembuatan handsanitizer telah memiliki pengetahuan dalam menerapan eksperimen ini menggunakan bahan organik. Siswa sangat terampil dan mendapatkan manfaat setelah melakukan pembuatan handsanitizer organik dari daun kelor sebesar 83,3%.